ANALYSIS OF POROUS STRUCTURE DESIGNS FOR IMPLANT APPLICATION USING ADDITIVE MANUFACTURING - ZAHARIN, HAIZUM AIMI (2019)
Active research indicates that, porous metal structures have emerged as a promising solution in biomedical application for repairing and replacing damaged bone. With the advent of additive manufacturing technology, fabrication of porous scaffold architecture of different unit cell types with desired parameters can replicate the biomechanical properties of the natural bone, thereby overcoming the issues, such as stress shielding effect, to avoid implant premature failure